Turkish validity and reliability study of the "respectful maternity care" knowledge and practice scale of midwives - Elif Dağlı; Feyza Aktaş Reyhan; Fatma Nilüfer Topkara; Maryam Moridi (Elsevier, 2023)
Objective: Increasing cesarean rates in Turkey show that respectful maternity care services should be given priority and importance. It is difficult to achieve sustainable development goals without adopting a respectful maternity care approach, and there is no Turkish measurement tool to evaluate the knowledge and practices of midwives on "respectful maternity care". The aim of this study is to evaluate whether the "respectful maternity care knowledge and practice scale of midwives" is an appropriate measurement tool for Turkish women by conducting a Turkish validity and reliability study. Study design: The methodological study was carried out by midwives working in three Public Hospitals. Data were collected face-to-face using the "introductory information form" and "the respectful maternity care knowledge and practice scale of midwives". Results: The scale consists of two sections knowledge and practice. Both sections have three sub-dimensions: "providing emotional support", "providing safe care", and "preventing abuse". The cronbach alpha internal consistency coefficient value ranged between 0.76 and 0.95 for both sections.This study has determined that this scale, which was adapted, consists of three sub-dimensions and 46 items (23 items each) in both knowledge and application sections, is a highly valid and reliable scale compatible with Turkish culture, as a result of the validity and reliability findings.